Host specificity of Aceria centaureae (Nalepa), a candidate for biological control of Centaurea dίffusa De Lamarck - Sobhian, R.; Katsouannos, Β. Ι.; Kashefi, J. (ENTOMOLOGIA HELLENICA, 1989)
Filed collected rosettes or twigs of Centaurea diffusa De Lamarck, infested by the gall mite Aceria centaureae, were fixed onto appropriately grown and planted test plants of ten different species in the area of Thessaloniki, Greece, in 1985 and 1986. The test plants were inspected for presence of galls and mites a few to several days after their contact with the infested twigs. Gall formation occurred on all of the Centaurea diffusa test plants, either of Greek or U.S. origin, and on some of the Centaurea solstitialis, L. test plants. No galls or other mite damage could be found on the other test plants, which were Carthamus tinctorius L. (safflower), Cirsiton creticion (De Lamarck) D’Urville, of local origin and six Cirsium species of U.S. origin, i.e. cymosum (Greene) J. T. Howell, occidentals (Nutt) Jeps., pastoris Howell, andersonii (Gray) Petrak, brevistylum Crong; and undulation (Nutt.) Spreng. These results suggest that A. centaureae most probably has a very restricted host plant range, feeding only on weedy Centaurea spp. Thus the mite should be considered as a possible candidate for biological control of diffuse knapweed in the U.S.A. and Canada.